2019
DOI: 10.1590/1980-0037.2019v21e59383
|View full text |Cite
|
Sign up to set email alerts
|

Predictive factors of the attack efficacy: the case of the Brazilian women’s Volleyball League champion team

Abstract: The aim was to identify the predictive factors of the attack efficacy of the Brazilian women’s League Champion team according to the level of performance of the opposing team.The sample was composed of the observation of 1137 attacks in 21 games of the 2015-2016 Brazilian women’s Volleyball League champion team. The results were significant to identify the predictive factors of the attack efficacy against high (.2=110.562; .<0.00001), intermediate (.2=64.134; .<0.00001) and low (.2=62.137; .<0.00001) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…39 Furthermore, with the insertion attack efficacy in each game complex, positive associations of KI, KII, KIII(1), KIII(2), KV(1) and KV(2) with point (E2), show the importance of adopting some risk in the serve and minimising errors in attack. 14,21,40,41 Using SNA and Eigenvector Centrality, in addition to providing an overview of all game complexes, [14][15][16][17] reinforced the need to investigate less well-studied complexes (i.e. KIII, KIV and KV).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…39 Furthermore, with the insertion attack efficacy in each game complex, positive associations of KI, KII, KIII(1), KIII(2), KV(1) and KV(2) with point (E2), show the importance of adopting some risk in the serve and minimising errors in attack. 14,21,40,41 Using SNA and Eigenvector Centrality, in addition to providing an overview of all game complexes, [14][15][16][17] reinforced the need to investigate less well-studied complexes (i.e. KIII, KIV and KV).…”
Section: Discussionmentioning
confidence: 99%
“…39 Furthermore, with the insertion attack efficacy in each game complex, positive associations of KI, KII, KIII(1), KIII(2), KV(1) and KV(2) with point (E2), show the importance of adopting some risk in the serve and minimising errors in attack. 14,21,40,41…”
Section: Discussionmentioning
confidence: 99%
“…Studies on match analysis in sports currently indicate a correlation between performance and game location [11,12], player experience [13,14], type of game played [13,15] game rules [15,16], offensive and defensive phases [4,17], team level [11,18], and other aspects inherent to the game context. Furthermore, it is observed that the analysis of tactical behaviors, for the most part, results from the interpretation of general metrics [19][20][21], examining the team's tactical behaviors that specify success or failure in the match [22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…In this context, the analysis of Complex I in volleyball underscores a relationship between reception and subsequent actions, such as the setting effectiveness [3,32], attack tempo [4,31,33], attack effect [10,19,33,34], and blocker number [4,9,33]. Furthermore, several studies indicate an association or prediction [23,24,33,[35][36][37] between the game actions of complex I, highlighting that receptions that allow an organized attack, quick settings, and powerful attacks culminate in attack point [33,[38][39][40].…”
Section: Introductionmentioning
confidence: 99%